2012
DOI: 10.1007/978-3-642-33119-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Improving Software Security Using Search-Based Refactoring

Abstract: Abstract. Security metrics have been proposed to assess the security of software applications based on the principles of "reduce attack surface" and "grant least privilege." While these metrics can help inform the developer in choosing designs that provide better security, they cannot on their own show exactly how to make an application more secure. Even if they could, the onerous task of updating the software to improve its security is left to the developer. In this paper we present an approach to automated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The minipatterns would be reused if applicable for other pattern transformations. The authors analyzed the (Gamma et al, 1994) patterns to determine whether a suitable transformation could be built with the applicable mini transformations. They found that while the tool generally worked well for the creational patterns, structural patterns and behavioral patterns caused problems.…”
Section: Survey Outlinementioning
confidence: 99%
See 3 more Smart Citations
“…The minipatterns would be reused if applicable for other pattern transformations. The authors analyzed the (Gamma et al, 1994) patterns to determine whether a suitable transformation could be built with the applicable mini transformations. They found that while the tool generally worked well for the creational patterns, structural patterns and behavioral patterns caused problems.…”
Section: Survey Outlinementioning
confidence: 99%
“…There is the method where problems are first detected in the code and then either refactoring options are generated in order to be applied manually Kessentini et al, 2012;Ouni et al, 2012;Wang et al, 2015;Mkaouer et al, 2016;Griffith et al, 2011) or the problems are addressed automatically (Di Penta, 2005). Koc et al, 2012;Mohan et al, 2016;O'Keeffe & Cinnéide, 2007b;Ghaith & Cinnéide, 2012;Cinnéide et al, 2012;Cinnéide et al, 2016;Veerappa & Harrison, 2013;Fatiregun et al, 2004) or again, using this approach to suggest refactorings to apply (Harman & Tratt, 2007;Seng et al, 2006;. Figure 5 identifies the number of papers that use each type of search technique, with GAs, GP and GEAs again encapsulated as EAs and PSO and ABC encapsulated as SOAs.…”
Section: Refactoring Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Ghannem et al [7] found appropriate refactoring suggestions using a set of refactoring examples. Their approach is based on an Interactive Genetic Algorithm which enables to interact with users and integrate their feedbacks into a classic GA. Ghaith et al [6] presented an approach to automate improvements of software security based on search-based refactoring. O'Keeffe et al [17] have constructed a software tool capable of refactoring objectoriented systems.…”
Section: Related Workmentioning
confidence: 99%